Relative phase stability: The interaction of attentional instruction and frequency on relative phase of bimanual coordination movements - Ehsan Zareıan (Selcuk University, 2016)
The present paper aimed to study the effect of using attentional instruction and increasing the rhythm on the relative phase stability of coordinated out-phase bimanual coordination movements. Using a plotter device, the participants (N=16) performed out-phase bimanual coordination pattern (45, 90, and 135 degree) while focusing on signs of the device (external attention) or their forearm (internal attention) or without attentional instruction with increasing frequency. KP was provided to participants after each attempt. Dependent variables were analyzed by 3 (attention) × 3 (relative phase) × 4 (frequency) analysis of variance with repeated measures on second and third variables. The results revealed that external attention lead to increased stability of relative phase in all three phase patterns. Additionally, increased frequency of motions caused decreased stability of relative in all three patterns. Findings of this study corroborated the constrained action hypothesis and showed that, unlike in-phase and anti-phase attractor patterns and because of the difficulty out-phase patterns, external attention instruction can act contrary to linear changes of control parameter and increase their stability of relative phases.